2015
DOI: 10.1111/1468-4446.12137
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing impacts of conspiracy theories on readers' political views: a rational choice perspective on anti‐semitic rhetoric inTurkey

Abstract: Although conspiracy theories have been politically significant throughout history, only a few empirical studies have been about their influence on readers' views. Combining a rational choice approach with a content analysis of an anti-Semitic best-selling conspiracy theory book series in Turkey - the Efendi series - and semi-structured interviews with its readers, this paper reveals the effects of the conspiracy theories on readers' political perspectives. The findings suggest that whereas the rightists are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…Perceptions of threat were associated with greater expressions of conspiracy theories, and people proposed conspiracy theories in line with their political arguments. Nefes () uncovered similar findings in an analysis of the communication of anti‐Semitic conspiracy rhetoric in Turkey. Further, using both quantitative and qualitative content analysis, Nefes () analyzed the relationship between people’s political views and online responses to the Turkish government’s conspiracy rhetoric about the Gezi Park protests in 2013.…”
Section: Definitionsmentioning
confidence: 61%
See 1 more Smart Citation
“…Perceptions of threat were associated with greater expressions of conspiracy theories, and people proposed conspiracy theories in line with their political arguments. Nefes () uncovered similar findings in an analysis of the communication of anti‐Semitic conspiracy rhetoric in Turkey. Further, using both quantitative and qualitative content analysis, Nefes () analyzed the relationship between people’s political views and online responses to the Turkish government’s conspiracy rhetoric about the Gezi Park protests in 2013.…”
Section: Definitionsmentioning
confidence: 61%
“…Simmons and Parsons () found that elites and masses are equally likely to traffic in specific conspiracy theories, and Uscinski & Parent () found that elites and masses follow similar patterns with their conspiracy discourse. Nefes () has shown that political party members in Turkey endorse or reject conspiracy theories based upon situational and ideological factors. With this said, insiders seem to be the scapegoats of much conspiracy theorizing in Western societies, so it would seem obvious that insiders would tend to reject conspiracy thinking.…”
Section: Definitionsmentioning
confidence: 99%
“…One group that has often been accused of conspiracy formation is the Jewish population. Jewish conspiracy theories—suggesting, for instance, that there is a Jewish plot to achieve world domination—still fuel anti-Semitism in various parts of the world, such as Malaysia ( Swami, 2012 ), Turkey ( Nefes, 2015 ), and Poland ( Golec de Zavala and Cichocka, 2012 ). Such conspiratorial anti-Semitism is a recurring issue throughout history.…”
Section: Historical Crises and Conspiracy Theoriesmentioning
confidence: 99%
“…Recent work has attempted to conceptualise conspiracy theories as both neutral, rational narratives of the world and the outcome of psychopathology (e.g., Nefes, 2015). In terms of the former, it is postulated that conspiracy theories offer simplistic explanations for individuals attempting to make sense of events that are confusing, difficult to comprehend, or poorly explained by mainstream sources of information .…”
Section: Introductionmentioning
confidence: 99%